Oxidative DNA damage as a potential marker for radiotherapy - Roszkowski, Krzysztof; Błaszczyk, Piotr (Contemporary Oncology/Współczesna Onkologia, 2009)
The products of cellular repair 8-oxo-7,8-dihydroguanine (8-oxoGua) and 8-oxo-7,8-dihydro-2\'-deoxyguanosine (8-oxodG) are excreted in urine. Reliable assays have been developed to measure urinary DNA lesions, such as HPLC pre-purification followed by gas chromatography/mass spectrometry (GC/MS). It is well known that ionizing radiation is a source of oxygen-derived species such as free radicals. Analysis of levels of 8-oxoGua and 8-oxodG in urine taken from patients before radiotherapy and at various times after irradiation should provide information about the efficiency of repair of oxidative DNA damage. Comparison of value level of these modifications with parameters estimating the success of therapy, such as the length of total survival or time to progression of disease, allows one to determine whether a cause-effect relationship exists between the efficiency of repair of radiotherapy-induced DNA damage and patient prognosis.